2019
DOI: 10.1101/649517
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Phlebotomus papatasisand fly salivary protein diversity and immune response potential in Egypt and Jordan populations

Abstract: 24 Phlebotomus papatasi sand flies inject their hosts with a myriad of pharmacologically active 25 salivary proteins to assist with blood feeding and to modulate host defenses. These salivary 26 proteins have been studied for their role in cutaneous leishmaniasis disease outcome with 27 different salivary proteins attenuating or exacerbating lesion size. Studies have shown that while 28 co-administered sand fly saliva exacerbates Leishmania major infections in naïve mice, animals 29 pre-exposed to saliva are p… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 76 publications
(93 reference statements)
0
1
0
Order By: Relevance
“…While previous studies demonstrated relatively low genetic differentiation between Ph. papatasi populations separated by large geographical distances [9,20], more recent studies have identified genetic differentiation between geographically separated populations [18, [21][22][23][24] and local differentiation [25]. Microsatellite analysis, in particular, revealed two distinct genetic clusters of Ph.…”
Section: Introductionmentioning
confidence: 99%
“…While previous studies demonstrated relatively low genetic differentiation between Ph. papatasi populations separated by large geographical distances [9,20], more recent studies have identified genetic differentiation between geographically separated populations [18, [21][22][23][24] and local differentiation [25]. Microsatellite analysis, in particular, revealed two distinct genetic clusters of Ph.…”
Section: Introductionmentioning
confidence: 99%